Analisis Balik Kestabilan Lereng Penampang A Dan Penampang B Area Lowwall Tambang Batubara Pada Pit X PT. Kideco Jaya Agung Kecamatan Batu Sopang Kabupaten Paser Provinsi Kalimantan Timur - Suryadi Putra; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT. Kideco Jaya Agung is a coal mine company in Paser Regency, East Kalimantan Province, with an Open Pit Mining method. Spreading cover rock is done by blasting. Blasting activities affect the slope of stability. In May 2018 there was a landslide in the A section lowwall area while cross section B in July 2018 occurred overcut to the design in 2018. In order to be able to provide the results of the analysis, several processes carried out were the calculation of blasting vibrations using the Matsuo reference formula. Then the back analysis using the probabilistic method of Monte Carlo. As well as analysis of safety factors and recommendations for slope geometry using janbu simplified method. The results of the analysis are (1) The relationship of the distance of blasting to Amaks produced is Amaks = -6 x 10-5 (distance) + 0.0416. (2) The geotechnical parameter of the back analysis is mudstone: c = 77,5 kN /m2 and Ф = 17,36; coal: c = 72,54 kN /m2 and Ф = 17,112. (3) Design of FK values in 2018 cross section A lowwall is 1,169 and crosswall B design 2018 FK design value is 1,365. (4) Recommendation of lowwall cross section A geometry with overall slope of 14o and make the width of the bench at an elevation of 65 mdpl above 30 meters.Keywords : Blasting, Back analysis, Monte carlo, Janbu simplified, Recommendations geometry of lowwall.